Three new species of the genus Neophyllobius Berlese (Acari: Camerobiidae) from Southern and Southwestern Iran - Khanjani, Mohammad (Zootaxa, 2013)
Three new species of the genus Neophyllobius Berlese, 1886 are described and illustrated from Iran: Neophyllobius ed-wardi sp. nov. and Neophyllobius seemani sp. nov. collected from soil under oak trees; and Neophyllobius dogani sp. nov. collected from soil under Astragalus bushes. A key to the species of Iran is provided.